A CRITICAL DISCOURSE ANALYSIS OF QUEEN’S "BOHEMIAN RHAPSODY" USING TEUN A. VAN DIJK’S MODEL - Chairani, Sri; Manugeren, M; Suhadi, Jumino; Purwarno, Purwarno (TELL - US JOURNAL, 2025)
This study applies Critical Discourse Analysis (CDA) to Bohemian Rhapsody by Queen, utilizing Teun A. van Dijk’s methodological framework. Since its release in 1975, the song has captivated audiences with its intricate composition and enigmatic lyrics, sparking diverse interpretations. This research explores how language and discourse within the lyrics reflect, construct, and challenge dominant ideologies and power structures. Through van Dijk’s model, the study examines the macrostructure, microstructure, and superstructure of the song in relation to social cognition and contextual influences. By analyzing linguistic choices, narrative elements, and intertextual meanings, the research reveals how the song navigates themes of identity, defiance, and existential turmoil. The findings indicate that Bohemian Rhapsody extends beyond its musical significance, functioning as a vehicle for cultural critique and social reflection. This study underscores the interdisciplinary relevance of CDA in music analysis, highlighting how discourse in popular songs both shapes and mirrors sociocultural dynamics, reinforcing their role in critical discourse studies.